2017
DOI: 10.1371/journal.pone.0179544
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Rickettsia Adr2 protein in E. coli is sufficient to promote resistance to complement-mediated killing, but not adherence to mammalian cells

Abstract: Bacteria exposed to host serum are subject to the antibacterial effects to the complement system. However, pathogenic microorganisms have evolved mechanisms of evading this immune attack. We have previously demonstrated that at least two R. conorii antigens, RC1281/Adr1 and OmpB β-peptide, contribute to the evasion of complement-mediated killing by binding the complement regulatory proteins vitronectin and factor H. RC1282/Adr2, a protein related to Adr1, is predicted to share similar structural features, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Among them, in Streptococcus pneumoniae serotype 3 strains, a central core of factor H-binding inhibitor of complement (Hic) (amino acid 151–201), a member of the pneumococcal surface protein C (PspC) family, interacts with VTN preventing the formation of the terminal complement complex 40 . In Rickettsia , RC1281/Adr1 and RC1282/Adr2 contributed to evasion of complement-mediated killing by binding to VTN and factor H 43 . The central region of Hic (the predicted binding site of VTN in the pneumococcal Hic molecule) 40 and the predicted surface exposed loops of the highly conserved outer membrane protein Adr2 in Rickettsia 43 bear no structural similarity with the far end C-terminal 18 residues of peptide-15 using the BLAST algorithm at NCBI ( https://blast.ncbi.nlm.nih.gov/Blast.cgi ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, in Streptococcus pneumoniae serotype 3 strains, a central core of factor H-binding inhibitor of complement (Hic) (amino acid 151–201), a member of the pneumococcal surface protein C (PspC) family, interacts with VTN preventing the formation of the terminal complement complex 40 . In Rickettsia , RC1281/Adr1 and RC1282/Adr2 contributed to evasion of complement-mediated killing by binding to VTN and factor H 43 . The central region of Hic (the predicted binding site of VTN in the pneumococcal Hic molecule) 40 and the predicted surface exposed loops of the highly conserved outer membrane protein Adr2 in Rickettsia 43 bear no structural similarity with the far end C-terminal 18 residues of peptide-15 using the BLAST algorithm at NCBI ( https://blast.ncbi.nlm.nih.gov/Blast.cgi ).…”
Section: Discussionmentioning
confidence: 99%
“…In Rickettsia , RC1281/Adr1 and RC1282/Adr2 contributed to evasion of complement-mediated killing by binding to VTN and factor H 43 . The central region of Hic (the predicted binding site of VTN in the pneumococcal Hic molecule) 40 and the predicted surface exposed loops of the highly conserved outer membrane protein Adr2 in Rickettsia 43 bear no structural similarity with the far end C-terminal 18 residues of peptide-15 using the BLAST algorithm at NCBI ( https://blast.ncbi.nlm.nih.gov/Blast.cgi ). Furthermore, although the impact of VTN glycosylation in SE36 binding needs to be clarified in future studies, oligosaccharide residues in VTN were also not required for binding of UspA2 and Hic in Moraxella catarrhalis and Streptococcus pneumoniae , respectively 40 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…1C ). This result demonstrates that, like other pathogenic rickettsial species, R. australis is resistant to bacteriolytic complement attack in naive serum ( 14 16 , 20 ) and that these bacteria are capable of acquiring the serum regulator vitronectin (see Fig. S1 in the supplemental material).…”
Section: Resultsmentioning
confidence: 72%
“…A recent report demonstrated that patients undergoing infection with the obligate intracellular bacterium R. conorii present with elevated levels of activated complement proteins ( 13 ). Additionally, rickettsial species express surface proteins that are sufficient to mediate resistance to the antibacterial effects of serum complement ( 14 16 , 20 ). We reasoned that while pathogenic Rickettsia species can activate complement, this class of pathogens have evolved mechanisms to resist complement-mediated killing during infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation